Osobennosti kommunikativnykh navykov doshkol'nikov s rasstroistvami autisticheskogo spektra - Konnova A. O. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2025)
The article explores contemporary theoretical frameworks related to the study of communicative characteristics in preschool-aged children with autism spectrum disorders (ASD). Particular emphasis is placed on the importance of timely intervention and personalized approaches that mitigate communicative challenges and enhance social adaptation. The discussion concludes with an exploration of potential directions for future research.
Keywords: взаимодействие; дошкольный возраст; коммуникация; коммуникативные способности; interaction; communication; preschool age; аутистический спектр; communicative abilities; autism spectrum